Incidencia de Leucemia Viral Felina en los gatos domésticos (Felis Silvestre Catus), atendidos en la Clínica Veterinaria Israel de la ciudad de Guayaquil. - Torres Montaño, Alexandra Elizabeth (2025)
The objective of this research was to determine the incidence of Feline Viral Leukemia in domestic cats (Felis Silvestre Catus) treated at the Israel Veterinary Clinic, in the city of Guayaquil. This was a quantitative and descriptive study, using immunochromatography as a diagnostic technique, a test that allows rapid detection of the virus. This viral disease directly affects the feline's immune system, facilitating the appearance of various secondary conditions such as lymphomas, fibrosarcomas, neuroblastomas, regenerative or hemolytic anemia, recurrent infections, gingivitis, stomatitis, weight loss and general weakness. For the statistical analysis, the nonparametric Pearson's Chi-square method was applied, with the support of Microsoft Excel. The sample consisted of 40 cats, of which 5 positive cases (12.5%) and 35 negative cases (87.5%) of the (100%) were identified, indicating a low incidence of the disease in the feline population studied. No statistically significant differences were found in relation to age, breed or sex, although male and mixed breed cats showed a slightly higher prevalence. Although Feline Viral Leukemia does not represent a direct risk to human health, it does constitute a public health problem due to the emotional and economic impact it represents for the owners, as well as to the welfare of the animals. The author recommends reinforcing prevention and awareness campaigns about the disease, encouraging vaccination, continuous education for guardians and the implementation of periodic diagnostic tests for more effective control of the disease. Key words: Feline Viral Leukemia, cats, incidence, risk factors, immunochromatograph.